Dynamics integrated control for four-wheel independent control electric vehicle. (30th July 2019) - Chen, Guoying; He, Lei; Zhang, Buyang; Hua, Min
Four-wheel independent control electric vehicle (FWIC-EV) as an emerging one has independent steering, driving and braking of each wheel. Apart from conventional vehicles, all independent chassis actuators drive-bywire allow vehicle dynamic improvement to assist the driver in enhancing handling and cornering stability. In this paper, a multilevel integrated control including motion controller and control allocation is introduced for the performance improvement. In the strategy, the motion controller based on model prediction control (MPC) optimises the vehicle control forces and moments within the actuators' characteristics and tracks the longitudinal and lateral references. According to the calculation of the MPC controller, the control allocation minimises each wheel's tyre workload, and distributes the wheels' steering angles and driving/braking torques. In the processing of the allocation, the constraints divided into equality and inequality constraints are introduced for simplification. On the basis of an FWIC-EV co-simulation vehicle model and an experimental platform, the performance of the multilevel integrated control is demonstrated